Variability, associations, path coefficient and stability analysis in poplar (Populus deltoides Bartr. ex Marsh) - Jha, Ramesh Kumar (Indian Journal of Agroforestry, 2020)
Forty genotypes were evaluated for growth characters at three location in Bihar. The significant difference was observed among the genotypes for all the characters under study. Wide range of genotypic coefficients of variation was noted for the character of survival, taper, number of leaves, internodal length, collar diameter, plant height and diameter of branches. Very high heritability was estimated for number of branches, angle of branches, total number of leaves and leaf area at all three locations. The expected genetic gain was observed the highest in number of branches followed by stem length at 1st branch at all three locations. Collar diameter showed significant positive correlation with height and positive association with number of branches, angle of branches, diameter of branches, length of branches, total number of leaves, leaf area and survival. Path coefficient analysis exhibited that number of branches had highest direct effect on collar diameter followed by leaf area, plant height, taper, diameter of branch, stem length at 1st branch and angle of branch. Stability analysis revealed that clones A-194, L-62/84 were stable genotypes over the sites.